Margaret Thatcher and the Middle East - Bermant, Azriel (Cambridge : Cambridge University Press, 2016)
Margaret Thatcher and the Middle East examines Thatcher's policy on the Middle East, with a spotlight on her approach towards the Israeli-Palestinian conflict. It questions claims that she sought to counter the Foreign Office Middle East policy, and maintains that the prime minister was actually in close agreement with the Whitehall bureaucracy on the Arab-Israeli conflict. In particular, the volume argues that Thatcher's concerns over Soviet ambitions in the Middle East encouraged her to oppose the policies of Israel's Likud governments, and to work actively for an urgent resolution of the conflict. Furthermore, while Thatcher was strongly pro-American, this was not translated into automatic support for Israel. Indeed, the Thatcher government was very much at odds with the Reagan administration over the Middle East, as a result of Washington's neglect of the forces of moderation in the region.
Introduction: Britain's colonial legacy and its postwar Middle East policy -- Thatcher and the'Finchley factor' -- The new Soviet threat -- Thatcher endorses the Venice Declaration -- Operation Babylon -- The crisis in Anglo-American relations -- Israel's invasion of Lebanon -- Thatcher's diplomatic initiative -- Thatcher's landmark visit to Israel -- The Reagan Administration spurns the London Agreement -- The collapse of the'Jordanian option' -- A new approach towards the PLO -- The end of a friendship -- Conclusion.
Title from publisher's bibliographic system (viewed on 11 Aug 2017).
Keywords: Great Britain -- Foreign relations -- Middle East; Middle East -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- 1979-1997.; Thatcher, Margaret -- Influence